2015
DOI: 10.1177/0960327115569809
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of cellular adenosine triphosphate and hepatocellular damage in rat after subchronic exposure to leachate from anthropogenic recycling site

Abstract: One of the major hazards arising from recycling sites is the generation of leachate containing mixed metal. This study evaluated the toxic effects of leachate obtained from Elewi Odo municipal auto-battery recycling site (EOMABRSL) on male liver functions using hepatic indices and biomarker of cellular adenosine triphosphate (ATP) in rat via the oral route. Concentrations of heavy metals analysis showed that lead, cadmium, nickel, chromium, manganese, and iron were 1.5-, 2-, 2.5-, 1.36-, 19.61-, and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…This discovery is line with recent development which reported that necrotic damage of the hepatic cells was responsible for the pathogenesis of the liver or its failure [37][38][39][40]. Also, another work reported that considerable damage to the hepatocytes was more pronounced in diabetic patients than physiological individuals [41].…”
Section: Discussionsupporting
confidence: 84%
“…This discovery is line with recent development which reported that necrotic damage of the hepatic cells was responsible for the pathogenesis of the liver or its failure [37][38][39][40]. Also, another work reported that considerable damage to the hepatocytes was more pronounced in diabetic patients than physiological individuals [41].…”
Section: Discussionsupporting
confidence: 84%
“…The increased level of hepatic enzymes may indicate degenerative changes and hypofunction of the liver [35,36] . In addition, a rise in plasma level of hepatic enzymes is an indication of liver damage especially when hepatic cells have undergone necrosis [37,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that co-administration of GAR, SACE or GAR plus SACE with lisinopril significantly attenuated the effects of this drug on the antioxidant enzymes and further suggest that lisinopril could cause impairment to hepatocytes through induction of oxidative stress. GSH plays a central role in the detoxification of xenobiotics and maintenance of the redox status of the cells [36] . A decline in its cellular level has been considered to be indicative of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eventually inhibits its wellness 1,5 . This has been implicated as one of the risk factors behind the low performance or absolute failure of the liver cells during in vivo metabolism of xenobiotic 6 .…”
mentioning
confidence: 99%